Transcriptome of Thalassicolla nucleata Holobiont Reveals Details of a Radiolarian Symbiotic Relationship - Liu, Zhenfeng; Mesrop, Lisa Y.; Hu, Sarah K.; Caron, David A. (Frontiers in Marine Science, 2019)
Radiolarians are a group of ubiquitous, yet poorly understood, large protists that often harbor photosymbionts. We studied the solitary radiolarian Thalassicolla nucleata by analyzing the transcriptome of its holobiont. We found that T. nucleata contained two dinoflagellate symbionts, one photosymbiont Brandtodinium sp., and one putative Peridiniales parasite. Through comparisons of gene expressions of Brandtodinium sp. and those of a close relative from a free-living culture, we found that the Brandtodinium sp. maintained its photosynthetic activities, but altered its carbon metabolism dramatically in hospite. Gene expression data also suggested carbon and nitrogen exchange between the host and photosymbiont and that lectin-glycan interaction might play an important role in host-symbiont recognition.